Influence of Relative Humidity and Oxygen Concentration on Corrosion Behaviour of Copper in H2S-Containing Liquid Petroleum Gas - Xianqiang Li; Yuan Lu; Qiang Wei; Hu Wang; Juan Xie (Metals, 2022)
In this paper, the influences of relative humidity (RH) and concentration of O2 on copper corrosion in H2S-containing LPG (liquid petroleum gas) were studied. The corrosion products obtained in different environments were also analysed by scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), grazing incidence X-ray diffraction (GIXRD), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR). In H2S-containing LPG, RH has pronounced influence on the corrosion grade of copper. The variation in the critical point (CP) with the RH of LPG is a linear relationship. The presence of O2 in dry H2S has limited influence on the corrosion of copper. In the presence of different RHs, the CP always follows a negative exponential function with O2 concentration. The analysis of different corrosion products implies different corrosion behaviours and mechanisms, which are dependent on the presence or absence of water vapour. The corrosion mechanisms obtained in four different environments were also proposed.